ECG changes at rest and during exercise in lowlanders with COPD travelling to 3100 m. (1st February 2021) - Carta, Arcangelo F.; Bitos, Konstantinos; Furian, Michael; Mademilov, Maamed; Sheraliev, Ulan; Marazhapov, Nuriddin H.; Lichtblau, Mona; Schneider, Simon R.; Sooronbaev, Talant; Bloch, Konrad E.; Ulrich, Silvia
Abstract: Background: The incidence and magnitude of cardiac ischemia and arrhythmias in patients with chronic obstructive pulmonary disease (COPD) during exposure to hypobaric hypoxia is insufficiently studied. We investigated electrocardiogram (ECG) markers of ischemia at rest and during incremental exercise testing (IET) in COPD-patients travelling to 3100 m. Study design and methods: Lowlanders (residence <800 m) with COPD (forced volume in the first second of expiration (FEV1 ) 40–80% predicted, oxygen saturation (SpO2 ) ≥92%, arterial partial pressure of carbon dioxide (PaCO2 ) <6 kPa at 760 m) aged 18 to 75 years, without history of cardiovascular disease underwent 12‑lead ECG recordings at rest and during cycle IET to exhaustion at 760 m and after acute exposure of 3 h to 3100 m. Mean ST-changes in ECGs averaged over 10s were analyzed for signs of ischemia (≥1 mm horizontal or downsloping ST-segment depression) at rest, peak exercise and 2-min recovery. Results: 80 COPD-patients (51% women, mean ± SD, 56.2 ± 9.6 years, body mass index (BMI) 27.0 ± 4.5 kg/m 2, SpO2 94 ± 2%, FEV1 63 ± 10% prEd.) were included. At 3100 m, 2 of 53 (3.8%) patients revealed ≥1 mm horizontal ST-depression during IET vs 0 of 64 at 760 m ( p  = 0.203). Multivariable mixed regression revealed minor but significant ST-depressions associated with altitude, peak exercise or recovery and rate pressure product (RPP) in multiple leads. Conclusion: In this study, ECG recordings at rest and during IET in COPD-patients do not suggest an increased incidence of signs of ischemia with ascent to 3100 m. Whether statistically significant ST changes below the standard threshold of clinical relevance detected in multiple leads reflect a risk of ischemia during prolonged exposure remains to be elucidated. Highlights: This is the first study on ECG-changes during exercise in COPD-patients at altitude. COPD-patients exposed 3–6 h to 3100 m did not reveal increased signs of ischemia. As potential risk factors, ST-depressions <1 mm were detected in multiple leads at 3100 m. 35% of COPD-patients reveal abnormal resting ECGs, which persist short-term at 3100 m.